2019
DOI: 10.1186/s13613-019-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive end-expiratory pressure titration with electrical impedance tomography and pressure–volume curve in severe acute respiratory distress syndrome

Abstract: BackgroundThe study objective was to compare titration of positive end-expiratory pressure (PEEP) with electrical impedance tomography (EIT) and with ventilator-embedded pressure–volume loop in severe acute respiratory distress syndrome (ARDS).MethodsWe have designed a prospective study with historical control group. Twenty-four severe ARDS patients (arterial oxygen partial pressure to fractional inspired oxygen ratio, PaO2/FiO2 < 100 mmHg) were included in the EIT group and examined prospectively. Data from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 39 publications
2
72
0
1
Order By: Relevance
“…It remains challenging for physicians to balance the regional recruitment and overdistension induced by PEEP. EIT has been used to assess the effect of PEEP on regional recruitment and overdistension in clinical practice [19][20][21][22][23]. Franchineau et al defined an optimal PEEP would keep regional collapse < 10% with minimum overdistension [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains challenging for physicians to balance the regional recruitment and overdistension induced by PEEP. EIT has been used to assess the effect of PEEP on regional recruitment and overdistension in clinical practice [19][20][21][22][23]. Franchineau et al defined an optimal PEEP would keep regional collapse < 10% with minimum overdistension [20].…”
Section: Discussionmentioning
confidence: 99%
“…Franchineau et al defined an optimal PEEP would keep regional collapse < 10% with minimum overdistension [ 20 ]. Zhao et al set the PEEP to the cross point of cumulated collapse and overdistension curve [ 22 ]. Both studies calculated collapse and overdistension according to the regional compliance curves along PEEP changes.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for EIT-guided PEEP titration increases pressure starting at 8 cmH 2 O with 2-min steps of 2 cmH 2 O till 20 cmH 2 O, and then decreases it with 2 cmH 2 O steps [ 4 ]. At each step, fractions of regional collapse and overdistention are calculated and the PEEP level selected (12 cmH 2 O) at the intercept point, to provide the best compromise between collapsed and overdistended lung (Fig.…”
Section: Case Presentationmentioning
confidence: 99%
“…Mauri et al [50] showed an improved homogeneous ventral-to-dorsal ventilation distribution during assisted ventilation at a high PEEP-level when compared with control mechanical ventilation. Zhao et al [51] compared individualized PEEP levels which were obtained from ODLC measurements to PEEP levels which were derived from global P/V curves (PEEP 2 cmH 2 O above LIP) and demonstrated that EIT-based PEEP titration might improve lung mechanics, gas exchange, and weaning success. ODLC measurements were also used to individually titrate PEEP in ARDS patients during ultra-protective mechanical ventilation (using a V T of 4 mL/kg BW or below) who underwent extra corporeal membrane oxygenation [52].…”
Section: Ventilation Monitoringmentioning
confidence: 99%